II. HADİS LİSANSÜSTÜ ÖĞRENCİ SEMPOZYUMU Covid-19 Sürecinde Çevrimiçi Bir Bilgi Şöleni - Eşi̇t, Musa (Dinî araştırmalar, 2020)
The second of the Ḥadith Graduate Student Symposium was held online on Thursday, 19 November 2020 this year. Ten papers were presented and discussed in four sessions at the symposium. The papers presented at the symposium are respectively "The Value of Criticism among Peer Hadith Narrators (Ravi) within the Scholarship of Jarh and Ta’dil" by Eymen Kamer; "Relationship between Shaybani and Shafi in the Framework of the Works Titled ‘Al-Hujja Ala Ahlil-Madinah’ and ‘Ikhtilafu Malik And Shafı’i’" by Ramazan Doğanay; "Bey’u’l Garar in The Light Of Hadiths" by Ayşe Boztaş; "An Evaluation on the Women’s Ways of Prayer" by Zeynep Sena Yılmaz; "Infectiousness of The Disease in the Teaching of Prophet Mohamed (Phub)" by Musa Eşit; "A Comparison in the Context of Faith: Example of Bukhari’s Sahih and Tirmizi’s Cami’" by Zehra İleri; "Evaluation of the Hadith Buhârî’s Emigrate to Abyssinia" by Ayşenur Gürtürk; "Bâkillânî’s Hadith Interpretation" by Lokman Korkut; "Abu al-Fayd Ahmad al-Ghumari and His Hadithions" by Mehmet Şakar; "Criticisms That are Directed to Work Named "Muqaddimah Ibn Al-Ṣalāḥ" and Evaluation of These Criticisms" by Hüseyin Yürekli.